2006
DOI: 10.1007/s10661-006-9231-8
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Sources of Polycyclic Aromatic Hydrocarbons in Surface Sediments Along the Egyptian Mediterranean Coast

Abstract: Coastal marine sediment samples were collected from 31 sampling stations along the Egyptian Mediterranean Sea coast. All sediment samples were analyzed to determine aliphatic and polycyclic aromatic hydrocarbons (PAHs) as well as total organic carbon (TOC) contents and grain size analysis. Total concentrations of 16 EPA-PAHs in the sediments were varied from 88 to 6338 ng g(-1) with an average value of 154 ng g(-1) (dry weight). However, the concentrations of total aliphatic were varied from 1.3 to 69.9 ng g(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 46 publications
(57 reference statements)
1
27
2
3
Order By: Relevance
“…The average concentrations of PAHs in the present study is lower than those recorded in the Egyptian Mediterranean coast with 88-6,338 ng/g; dry weight (El Nemr et al 2007), and than those observed by Baumard et al (1998) in Barcelona; Spain with 1,700 ng/g; dry weight and Port Vendres; France with 6,900 ng/g; dry weight. Most sampling sites in Abu Qir Bay were contaminated in the range 146-1,447 ng/g (dry weight) except at station E, in front of the Electric Power Station (EPS) with 95 ng/g (dry weight), which may be due to thermal pollution resulted from cooling water of the EPS station.…”
Section: Resultscontrasting
confidence: 82%
“…The average concentrations of PAHs in the present study is lower than those recorded in the Egyptian Mediterranean coast with 88-6,338 ng/g; dry weight (El Nemr et al 2007), and than those observed by Baumard et al (1998) in Barcelona; Spain with 1,700 ng/g; dry weight and Port Vendres; France with 6,900 ng/g; dry weight. Most sampling sites in Abu Qir Bay were contaminated in the range 146-1,447 ng/g (dry weight) except at station E, in front of the Electric Power Station (EPS) with 95 ng/g (dry weight), which may be due to thermal pollution resulted from cooling water of the EPS station.…”
Section: Resultscontrasting
confidence: 82%
“…This may be explained in view of the observed inverse correlation between DO and BOD which is attributed to the consumption of DO by microorganism such as aerobic bacteria in presence of high organic matter, ammonia and/ or eutrophic conditions [20]. Due to the existence of oxygen-consuming materials in fresh water inflows much more than in seawater inflows, [4,12] DO is consumed in water of low salinity more than in that of high salinity. Moreover, during summer, considering the highly significant positive correlations found between BOD vs. PI and TIN; and ammonia vs. TIN whereas highly significant negative correlations found between DO vs. ammonia and TIN; and nitrate vs. EC, TDS, salinity and Cl, it may be concluded that ammonia was the main O 2 consumer via bio-oxidation to nitrate in lower salinity water.…”
Section: Statistical Correlationmentioning
confidence: 99%
“…On the other hand, the highest contents of total polycyclic aromatic hydrocarbons (TPAHs) in the surface sediments along the Egyptian Mediterranean coast were found in the seashore near Manzala Lake; 4895-6338 ng g−1 [12].…”
mentioning
confidence: 99%
“…They have been classified as priority pollutants by national and international environmental agencies (e.g., EPA-US, EEA-EU) since certain homologues are highly carcinogenic and mutagenic, exhibiting tendency to bioaccumulate in aquatic organisms (Samanta et al, 2002). PAHs' formation and release in the environment is related to various anthropogenic activities including pyrolysis/combustion of organic material (biomass burning, incomplete combustion of fossil fuels) and release of petroleum products (Neff, 1979;Simoneit, 1984;Yunker et al, 2002;and references therein). PAHs of biogenic origin may also occur in environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic hydrocarbons and PAHs have been investigated over the last decades in surficial sediments of the EMS, primarily in coastal or shallow basin sites in the Aegean Sea, southern Italy, the coast of Egypt and the Adriatic Sea (Aboul-Kassim and Simoneit, 1995;Alebic-Juretic, 2011;Botsou and Hatzianestis, 2012;Cardellicchio et al, 2007;Gogou et al, 2000;Gonul and Kucuksezgin, 2012;Guzzella and De Paolis, 1994;Marcomini et al, 1986;Nemr et al, 2007;Sklivagou et al, 2008;Yilmaz et al, 1998). However, there is an important lack of data regarding their occurrence in deep basins, which might represent a long-term sink for hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%